Have a Little Faith
A third wonderfully moving novel from internationally bestselling author Mitch Albom, whose books have touched the hearts of millions around the world. A compelling exploration of faith and spirituality - always moving, often profound - is the cornerstone of Albom\\\'s work. Have a Little Faith, like his first two novels, is a poignant and inspiring read - one that will enchant fans old and new.